High Performance of Enzymatic Bioprocess for Production of Biomassed-based Bioethanol of Sago Palm Fiber Waste - Nani Harihastuti; Rame Rame; Silvy Djayanti (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2018)
Biomass waste in the form of fiber dregs contains many components of lignocellulose and hemicellulose. Lignocellulose can be used to produce ethanol through enzymatic biotechnology processes. Sago palm fiber industry is one potential industry producing biomass waste in the form of solid waste of fiber dregs (about 30% from the weight of processed raw materials). Solid fiber waste contains crude fiber and lignocellulose compound consists of cellulose (35-50%), hemicellulose ( 20-35%) and lignin (12-20%). This study aimed to utilize solid waste of sago palm fiber as a raw material of bioethanol production through enzymatic biotechnology processes of delignification, saccharification and fermentation which was then purified by distillation process to get ethanol. Delignification, saccharification, and fermentation stages are conducted using Phanerochaete chrysosporus Mushroom, Trichoderma viride fungus, and saccharomyces cerevisiae, respectively and then purified by distillation process (one level) to produce ethanol. The process of saccharification and fermentation process were done in an integrated manner (addition of Trichoderma viride and yeast saccharomyces cereviceae fungi done simultaneously). The weight of raw materials of solid waste fiber treated was about 6 kgs. Alcohol content obtained was about ± 4% (distillation). No water, air, and soil pollution inflicted, more added value, and sustainable were the main benefits of biotech process or bioprocess.